Electromagnetic shielding composite material for winding forming process and preparation method thereof

By introducing Ti3C2TX nanosheets, silver nanowires and metal nanoparticles in the winding molding process, an efficient conductive network was built, which solved the problems of poor shielding effect of existing electromagnetic shielding composite materials and complex molding processes, and achieved efficient electromagnetic shielding and excellent Combination of mechanical properties.

CN119307068AActive Publication Date: 2025-01-14CHENGDU LUCHEN NEW MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411664822.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-14
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The shielding effect of existing electromagnetic shielding composite materials is poor and the molding process is complicated, making it difficult to meet the demand for electromagnetic wave shielding of modern electronic equipment.

Method used

By introducing two-dimensional Ti3C2TX nanosheets and one-dimensional silver nanowires in the winding molding process, an efficient conductive network is built, and the continuity and integrity of the conductive network is enhanced by using metal nanoparticles, reducing the amount of metal conductive filler added, and simplifying the process process.

Benefits of technology

It significantly improves the electromagnetic shielding efficiency and mechanical properties of composite materials, ensures excellent electromagnetic shielding function and good mechanical strength and toughness, and simplifies the production process, reduces costs and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307068A_ABST
    Figure CN119307068A_ABST
Patent Text Reader

Abstract

The invention discloses an electromagnetic shielding composite material for a winding forming process and a preparation method of the electromagnetic shielding composite material, and belongs to the technical field of resin-based composite materials. The preparation method comprises the following steps: sequentially adding LiF and a Ti3AlC2 precursor into a hydrochloric acid solution, and carrying out a stirring reaction to obtain Ti3C2TX; the preparation method comprises the following steps: adding a diluent and silver nanowires into epoxy resin, and uniformly stirring to obtain a premix 1; ti3C2TX and metal nanoparticles are added into a curing agent and subjected to ultrasonic treatment, and a premix 2 is obtained; and uniformly mixing the premix 1, the premix 2 and the accelerant to obtain the feed. The invention further discloses the electromagnetic shielding composite material prepared by the method and used for the winding forming process. The electromagnetic shielding composite material for the winding forming process has relatively good overall mechanical properties and electromagnetic shielding effectiveness, and is wide in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of resin-based composite materials, and in particular relates to an electromagnetic shielding composite material used in a winding molding process and a preparation method thereof. Background Art

[0002] Wet winding molding refers to a composite material molding method in which the reinforcing material is directly wound on the core mold after being impregnated with resin and then formed after curing. As an efficient composite material manufacturing method, it is widely used in many fields such as aerospace, national defense and military, petroleum and chemical industry, marine engineering, automobile and energy due to its high molding precision, light product quality, high strength, overall molding and high production efficiency.

[0003] With the advancement of technology and the development of new materials, the application areas of winding molding are also expanding. Electronic equipment inside satellites and spacecraft, electronic control parts of missiles and weapon systems, inside missile launch tubes, medical imaging equipment, communication base stations, antenna towers and other equipment all need to shield external electromagnetic waves to ensure the normal operation of the equipment, which puts forward new requirements for some winding molding products.

[0004] In order to give the wound product an electromagnetic shielding function, a conductive or magnetic material layer can be added during the winding process. These materials can be metal fibers, conductive polymers or composite materials containing conductive metal particles, such as adding metal foil during the winding process or spraying a conductive coating on the surface of the finished product. This method requires additional steps, and the conductive layer is poorly bonded to the product, resulting in poor shielding effect. In addition, the electromagnetic shielding function can also be achieved by adding conductive fillers to the resin system, but the amount of filler added is large, resulting in high resin viscosity, affecting the molding process, and not in line with the development trend of lightweighting. Summary of the invention

[0005] The problem to be solved by the present invention is to provide an electromagnetic shielding composite material for winding molding process and a preparation method thereof, so as to solve the problems of poor shielding effect and complicated molding process of existing electromagnetic shielding composite materials.

[0006] The technical solution adopted to solve the technical problem is to provide a method for preparing an electromagnetic shielding composite material for a winding molding process, comprising the following steps: (1) LiF and Ti3AlC2 precursors were added to the hydrochloric acid solution in sequence and stirred to obtain Ti3C2T X ; (2) adding the diluent and the silver nanowires into the epoxy resin and stirring evenly to obtain a premix 1; (3) Ti3C2T X and metal nanoparticles are added to the curing agent and ultrasonicated to obtain premix 2; (4) The premix 1, the premix 2 and the accelerator are mixed to obtain an electromagnetic shielding composite material for winding molding process.

[0007] The beneficial effects of the above technical solution of the present invention are as follows: X Metal nanoparticles are anchored on the nanosheets, which increases the roughness of the sheet and improves the electromagnetic shielding performance. At the same time, one-dimensional silver nanowires are introduced into the resin matrix, and their welding effect is used to construct an interconnected three-dimensional conductive network. While reducing the amount of metal conductive filler added to the system, the integrity of the conductive network is ensured, giving the wound product excellent electromagnetic shielding function. In addition, the formation of a three-dimensional network improves the overall mechanical properties of the material. This structural advantage enables the composite material to have good mechanical strength and toughness while maintaining excellent electromagnetic shielding performance. In the preparation method, LiF and Ti3AlC2 precursors are added to the hydrochloric acid solution for stirring reaction, and the two-dimensional Ti3C2T X Materials, ensuring Ti3C2T X The high conductivity and good dispersibility of Ti3C2T4 provide a basis for the subsequent electromagnetic shielding performance of the composite material; then the diluent and silver nanowires are added to the epoxy resin and stirred evenly to ensure the uniform dispersion of the silver nanowires in the resin matrix and avoid agglomeration, thereby improving the conductivity and electromagnetic shielding effectiveness of the composite material; Ti3C2T4 X The metal nanoparticles are added into the curing agent process so that the metal nanoparticles are anchored on Ti3C2T X The continuity and integrity of the conductive network are further enhanced; finally, the accelerator is added to avoid premature curing between premixes and affect the performance of the composite material.

[0008] Preferably, in step (1), the molar ratio of Ti3AlC2 precursor to LiF is 1:(5-7.5); the stirring reaction temperature is 35-45°C, and the time is 24-48h; Ti3C2T X The size is 100nm~3μm.

[0009] Preferably, after the stirring reaction in step (1), the mixture is washed with water and centrifuged until the pH of the upper layer is greater than 6, and then the lower layer precipitate is cooled, ultrasonicated with water, and centrifuged again.

[0010] Preferably, the rotation speed of the two centrifugations is 3000-6000 rpm, the time is 10-15 min; the cooling temperature is 2-4° C., the time is 2-6 h; and the water addition and ultrasonication time is 30-60 min.

[0011] Preferably, the diluent is dibutyl alcohol diglycidyl ether; the epoxy resin is 4,4'-dihydroxydiphenylmethane; the diameter of the silver nanowire is 20-25 nm and the length is 15-30 μm; the metal nanoparticles are copper nanoparticles and / or silver nanoparticles; the curing agent is methyltetrahydrophthalic anhydride; and the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol.

[0012] Preferably, the mass ratio of epoxy resin, diluent, curing agent and accelerator is (100-105):(85-95):(80-90):(1-2).

[0013] More preferably, Ti3C2T X The addition amount of silver nanowires is 1~3% of the total mass of the electromagnetic shielding composite material used for the winding molding process; the addition amount of metal nanoparticles is 0.3~1% of the total mass of the electromagnetic shielding composite material used for the winding molding process.

[0014] Preferably, in step (2), the stirring temperature is 40-65° C. and the stirring time is 3-6 h.

[0015] Preferably, the ultrasonication in step (3) is ice bath ultrasonication for 0.5 to 3 h.

[0016] The present invention also provides an electromagnetic shielding composite material used in a winding molding process and obtained by the above preparation method.

[0017] The present invention has the following beneficial effects: (1) In the preparation process of the electromagnetic shielding composite material for winding molding process of the present invention, two-dimensional Ti3C2T X The material and highly conductive silver nanowires and metal nanoparticles are introduced into the composite material to construct an efficient conductive network, which significantly improves the electromagnetic shielding effectiveness of the composite material, ensures the stability and durability of the shielding effect, and meets the demand for high-performance electromagnetic shielding materials.

[0018] (2) In the electromagnetic shielding composite material for winding molding process of the present invention, Ti3C2T X The combination of the two-dimensional structure of the composite material and the one-dimensional characteristics of the silver nanowires not only enhances the conductivity of the composite material, but also improves the overall mechanical properties of the material through their synergistic effect. This structural advantage enables the composite material to have good mechanical strength and toughness while maintaining excellent electromagnetic shielding performance.

[0019] (3) In the preparation method of the present invention, each component is introduced and uniformly mixed at an appropriate stage without the need for complicated additional process steps, which not only simplifies the production process and reduces production costs, but also improves production efficiency, thus providing the possibility for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The shielding effectiveness diagram of the electromagnetic shielding composite material used in the winding molding process of Examples 1 to 5 and Comparative Examples 1 to 3; Figure 2 This is a graph showing the electromagnetic shielding performance of wound products with different thicknesses. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments.

[0022] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.

[0023] The features and performance of the present invention are further described in detail below in conjunction with embodiments.

[0024] Example 1 A method for preparing an electromagnetic shielding composite material for a winding molding process comprises the following steps: (1) 8.5 g of LiF was added to the hydrochloric acid solution and stirred evenly, and then 10 g of Ti3AlC2 precursor was added and stirred evenly, and then argon was introduced to seal the solution, and the reaction was stirred at 35°C for 24 h. After the reaction, the solution was washed with water and centrifuged at 3500 rpm for 10 min until the pH of the upper liquid was greater than 6. The lower precipitate was then cooled at 3°C ​​for 5 h, and then water was added to fully shake it, and then ice-bathed for 60 min, and then centrifuged at 3500 rpm for 10 min again to obtain Ti3C2T with a size of 100 nm~3 μm. X ; (2) adding 900 g of dibutyl alcohol diglycidyl ether and 40.5 g of silver nanowires with a diameter of 20-25 nm and a length of 15-30 μm to 1000.5 g of 4,4′-dihydroxydiphenylmethane, stirring at 50° C. for 4 h until uniform, and cooling to room temperature to obtain premix 1; (3) 90.3 g of Ti3C2TX and 16 g of copper nanoparticles were added to 850 g of methyltetrahydrophthalic anhydride and ultrasonicated in an ice bath for 2 h to obtain premix 2; (4) Premix 1 and premix 2 were mixed, and 15.3 g of 2,4,6-tris(dimethylaminomethyl)phenol was added and mixed evenly to obtain an electromagnetic shielding composite material for winding molding process.

[0025] Example 2 A method for preparing an electromagnetic shielding composite material for a winding molding process comprises the following steps: (1) 8.1 g of LiF was added to the hydrochloric acid solution and stirred evenly, and then 10.5 g of Ti3AlC2 precursor was added and stirred evenly, and then argon was introduced to seal the solution, and the reaction was stirred at 35°C for 48 h. After the reaction, the solution was washed with water and centrifuged at 5000 rpm for 10 min until the pH of the upper liquid was greater than 6. The lower precipitate was then cooled at 3°C ​​for 5 h, and then water was added to fully shake it, and then it was ultrasonicated in an ice bath for 30 min, and then centrifuged at 5000 rpm for 10 min again to obtain Ti3C2T with a size of 100 nm~3 μm. X ; (2) adding 900.6 g of dibutyl alcohol diglycidyl ether and 60.3 g of silver nanowires with a diameter of 20-25 nm and a length of 15-30 μm to 1001 g of 4,4′-dihydroxydiphenylmethane, stirring at 50° C. for 4 h until uniform, and cooling to room temperature to obtain premix 1; (3) 140.5 g of Ti3C2T X and 20.2 g of copper nanoparticles were added to 850 g of methyltetrahydrophthalic anhydride and ultrasonicated in an ice bath for 2 h to obtain premix 2; (4) Premix 1 and premix 2 were mixed, and 15.3 g of 2,4,6-tris(dimethylaminomethyl)phenol was added and mixed evenly to obtain an electromagnetic shielding composite material for winding molding process.

[0026] Example 3 A method for preparing an electromagnetic shielding composite material for a winding molding process comprises the following steps: (1) 10.3 g of LiF was added to the hydrochloric acid solution and stirred evenly, and then 10 g of Ti3AlC2 precursor was added and stirred evenly, and then argon was introduced to seal the solution, and the reaction was stirred at 45 ° C for 48 h. After the reaction, the solution was washed with water and centrifuged at 5000 rpm for 10 min until the pH of the upper liquid was greater than 6. Then, the lower precipitate was cooled at 3 ° C for 5 h, and then water was added to fully shake it, and then ice bath ultrasonic was performed for 30 min, and then centrifuged at 5000 rpm for 10 min again to obtain Ti3C2T with a size of 100 nm~3 μm. X ; (2) adding 900.7 g of dibutyl alcohol diglycidyl ether and 40.6 g of silver nanowires with a diameter of 20-25 nm and a length of 15-30 μm to 1001.2 g of 4,4′-dihydroxydiphenylmethane, stirring at 50° C. for 4 h until uniform, and cooling to room temperature to obtain premix 1; (3) 90.2 g of Ti3C2T X and 15.9 g of copper nanoparticles were added to 850 g of methyltetrahydrophthalic anhydride and ultrasonicated in an ice bath for 2 h to obtain premix 2; (4) Premix 1 and premix 2 were mixed, and 15.1 g of 2,4,6-tris(dimethylaminomethyl)phenol was added and mixed evenly to obtain an electromagnetic shielding composite material for winding molding process.

[0027] Example 4 A method for preparing an electromagnetic shielding composite material for a winding molding process comprises the following steps: (1) 10.3 g of LiF was added to the hydrochloric acid solution and stirred evenly, and then 10 g of Ti3AlC2 precursor was added and stirred evenly, and then argon was introduced to seal the solution, and the reaction was stirred at 45 ° C for 48 h. After the reaction, the solution was washed with water and centrifuged at 5000 rpm for 10 min until the pH of the upper liquid was greater than 6. Then, the lower precipitate was cooled at 3 ° C for 5 h, and then water was added to fully shake it, and then ice bath ultrasonic was performed for 30 min, and then centrifuged at 5000 rpm for 10 min again to obtain Ti3C2T with a size of 100 nm~3 μm. X ; (2) adding 901 g of dibutyl alcohol diglycidyl ether and 60 g of silver nanowires with a diameter of 20-25 nm and a length of 15-30 μm to 1000.5 g of 4,4′-dihydroxydiphenylmethane, stirring at 50° C. for 4 h until uniform, and cooling to room temperature to obtain premix 1; (3) 140.1 g of Ti3C2T X and 19.9 g of copper nanoparticles were added to 850 g of methyltetrahydrophthalic anhydride and ultrasonicated in an ice bath for 3 h to obtain premix 2; (4) Premix 1 and premix 2 are mixed, and 15 g of 2,4,6-tris(dimethylaminomethyl)phenol is added and mixed evenly to obtain an electromagnetic shielding composite material for winding molding process.

[0028] Example 5 A method for preparing an electromagnetic shielding composite material for a winding molding process comprises the following steps: (1) 10 g of LiF was added to the hydrochloric acid solution and stirred evenly, then 10.1 g of Ti3AlC2 precursor was added and stirred evenly, then argon was introduced to seal the mixture, and the mixture was stirred and reacted at 45 °C for 30 h. After the reaction, the mixture was washed with water and centrifuged at 3500 rpm for 10 min until the pH of the upper liquid was greater than 6. The lower precipitate was then cooled at 3 °C for 5 h, and then water was added to fully shake the mixture, followed by ice bath ultrasonication for 30 min, and then centrifuged at 3500 rpm for 10 min to obtain Ti3C2T with a size of 100 nm to 3 μm. X ; (2) adding 900.6 g of dibutyl alcohol diglycidyl ether and 50.6 g of silver nanowires with a diameter of 20-25 nm and a length of 15-30 μm to 1001.5 g of 4,4′-dihydroxydiphenylmethane, stirring at 50° C. for 4 h until uniform, and cooling to room temperature to obtain premix 1; (3) 119.8 g of Ti3C2T X and 29.1 g of copper nanoparticles were added to 850 g of methyltetrahydrophthalic anhydride and ultrasonicated in an ice bath for 3 h to obtain premix 2; (4) Premix 1 and premix 2 are mixed, and 15 g of 2,4,6-tris(dimethylaminomethyl)phenol is added and mixed evenly to obtain an electromagnetic shielding composite material for winding molding process.

[0029] Comparative Example 1 A method for preparing an electromagnetic shielding composite material for a winding molding process comprises the following steps: Take 1000.9 g of 4,4'-dihydroxydiphenylmethane, add 901.2 g of dibutyl alcohol diglycidyl ether, 849.3 g of methyltetrahydrophthalic anhydride and 15 g of 2,4,6-tris(dimethylaminomethyl)phenol to 4,4'-dihydroxydiphenylmethane at room temperature, stir evenly, and obtain the product.

[0030] Comparative Example 2 A method for preparing an electromagnetic shielding composite material for a winding molding process comprises the following steps: (1) 8.5 g of LiF was added to the hydrochloric acid solution and stirred evenly, and then 10 g of Ti3AlC2 precursor was added and stirred evenly, and then argon was introduced to seal the solution, and the reaction was stirred at 35°C for 24 h. After the reaction, the solution was washed with water and centrifuged at 3500 rpm for 10 min until the pH of the upper liquid was greater than 6. The lower precipitate was then cooled at 3°C ​​for 5 h, and then water was added to fully shake it, and then ice-bathed for 60 min, and then centrifuged at 3500 rpm for 10 min again to obtain Ti3C2T with a size of 100 nm~3 μm. X ; (2) 90g of Ti3C2T Xand 16 g of copper nanoparticles were added to 850.5 g of methyltetrahydrophthalic anhydride and ultrasonicated in an ice bath for 2 h to obtain a premix; (3) Add 1001 g of 4,4'-dihydroxydiphenylmethane, 900.2 g of dibutyl alcohol diglycidyl ether and 15.1 g of 2,4,6-tris(dimethylaminomethyl)phenol to the premix in sequence and stir evenly to obtain the product.

[0031] Comparative Example 3 A method for preparing an electromagnetic shielding composite material for a winding molding process comprises the following steps: Take 1000g of 4,4'-dihydroxydiphenylmethane, add 899.6g of dibutyl alcohol diglycidyl ether and 40.5g of silver nanowires with a diameter of 20-25nm and a length of 15-30μm, stir at 50°C for 4h, cool to room temperature, add 850.5g of methyltetrahydrophthalic anhydride and 15.2g of 2,4,6-tris(dimethylaminomethyl)phenol, stir evenly, and obtain.

[0032] Experimental example 1. Mechanical properties test The electromagnetic shielding composite materials for winding molding process prepared in the above Examples 1 to 5 and Comparative Examples 1 to 3 were placed in a vacuum oven for defoaming treatment for 1 hour, and then poured and cured according to the curing system: 60°C / 1h+80°C / 1h+150°C / 2h to obtain specimens, and their mechanical properties were tested according to GB / T 2567 standard. The results are shown in Table 1.

[0033] Table 1 Mechanical properties test results

[0034] It can be seen from Table 1 that the tensile strength, flexural strength and impact toughness of the electromagnetic shielding composite material used in the winding molding process of the present invention are significantly better than those of the electromagnetic shielding composite materials prepared in Comparative Examples 1 to 3. This is because the present invention introduces two-dimensional Ti3C2T X and one-dimensional silver nanowires, while reducing the amount of metal conductive filler added, the structural network integrity is further improved, and its mechanical properties are better.

[0035] 2. Magnetic shielding performance test A square cylinder mold was selected, glass fiber yarn was selected as the reinforcing material, the number of yarn balls was 8, the tension control was set to 10N / ball, the temperature of the glue tank was controlled at 35±3℃, the winding was carried out according to the established procedure, the product thickness was controlled at 2mm, and it was cured according to the procedure of 60℃ / 1h+80℃ / 1h+150℃ / 2h. The specimens were cut and the shielding effectiveness within the X-band frequency range was tested using the N5247A PNA vector network analyzer. The results are as follows Figure 1 As shown. Taking the electromagnetic shielding composite material for winding molding process prepared in Example 1 as the research object, a series of winding products with different thicknesses (1mm, 2mm, 3mm, 4mm, 5mm) were prepared under the same winding process, and the electromagnetic shielding effectiveness of the corresponding thickness was tested. The results are shown in Figure 2 shown.

[0036] from Figure 1 It can be seen that the introduction of Ti3C2T X The electromagnetic shielding effectiveness of the wound product with metal nanoparticles is 30.2dB, and the shielding effectiveness of the wound product with silver nanowires is 21.6dB. X The electromagnetic shielding effectiveness of the products obtained by adding and removing metal nanoparticles is greater than 53.9dB, and the maximum can reach 60.6dB, which shows excellent shielding effectiveness. This is because the introduction of silver nanowires alone, due to the limited addition amount and weak interaction between nanowires, makes the formed conductive network loose; the introduction of Ti3C2T X The two-dimensional sheets are adhered to each other, so the system reflects less electromagnetic waves. X By introducing metal nanoparticles into the winding products and utilizing the welding effect of silver nanowires, a tighter and more complete three-dimensional conductive network is obtained. At the same time, the metal nanoparticles increase the roughness of the two-dimensional sheets, improve the reflection and absorption of electromagnetic waves, and thus greatly improve the electromagnetic shielding effectiveness.

[0037] from Figure 2 It can be seen that as the thickness of the product increases, the shielding effectiveness further increases. This is because the winding process makes the conductive filler well dispersed in the product. As the thickness increases, the reflection and absorption of electromagnetic waves by the product are further enhanced, and the shielding effectiveness increases accordingly.

[0038] The present invention has been described according to the above embodiments. It should be understood that the above embodiments do not limit the present invention in any form. Any technical solutions obtained by equivalent replacement or equivalent transformation shall fall within the scope of the present invention.

Claims

1. A method for preparing an electromagnetic shielding composite material for a winding molding process, characterized in that: The following steps are involved: (1) LiF and Ti3AlC2 precursors were added to the hydrochloric acid solution in sequence and stirred to obtain Ti3C2T X ; (2) adding the diluent and the silver nanowires into the epoxy resin and stirring evenly to obtain a premix 1; (3) Ti3C2T X and metal nanoparticles are added to the curing agent and ultrasonicated to obtain premix 2; (4) The premix 1, the premix 2 and the accelerator are mixed to obtain an electromagnetic shielding composite material for winding molding process.

2. The method for preparing an electromagnetic shielding composite material for winding molding process according to claim 1, characterized in that: The molar ratio of the Ti3AlC2 precursor to LiF in step (1) is 1:(5-7.5); the stirring reaction temperature is 35-45°C and the reaction time is 24-48h; the Ti3C2T X The size is 100nm~3μm.

3. The method for preparing an electromagnetic shielding composite material for winding molding process according to claim 1, characterized in that: In the step (1), after the reaction is stirred, the mixture is washed with water and centrifuged until the pH of the upper layer is greater than 6, and then the lower layer of precipitation is cooled, ultrasonicated with water, and centrifuged again.

4. The method for preparing an electromagnetic shielding composite material for winding molding process according to claim 3, characterized in that: The rotation speed of the two centrifugations is 3000-6000 rpm, and the time is 10-15 min; the cooling temperature is 2-4° C., and the time is 2-6 h; and the water addition ultrasound time is 30-60 min.

5. The method for preparing an electromagnetic shielding composite material for winding molding process according to claim 1, characterized in that: The diluent is dibutyl alcohol diglycidyl ether; the epoxy resin is 4,4'-dihydroxydiphenylmethane; the diameter of the silver nanowire is 20-25 nm and the length is 15-30 μm; the metal nanoparticles are copper nanoparticles and / or silver nanoparticles; the curing agent is methyltetrahydrophthalic anhydride; and the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol.

6. The method for preparing an electromagnetic shielding composite material for winding molding process according to claim 1 or 5, characterized in that: The mass ratio of the epoxy resin, diluent, curing agent and accelerator is (100-105):(85-95):(80-90):(1-2).

7. The method for preparing an electromagnetic shielding composite material for winding molding process according to claim 1 or 5, characterized in that: The Ti3C2T X The addition amount of the silver nanowire is 1-3% of the total mass of the electromagnetic shielding composite material used for the winding molding process; the addition amount of the metal nanoparticles is 0.3-1% of the total mass of the electromagnetic shielding composite material used for the winding molding process.

8. The method for preparing an electromagnetic shielding composite material for winding molding process according to claim 1, characterized in that: In the step (2), the stirring temperature is 40-65° C. and the stirring time is 3-6 hours.

9. The method for preparing an electromagnetic shielding composite material for winding molding process according to claim 1, characterized in that: The ultrasonication in step (3) is ice bath ultrasonication, and the time is 0.5 to 3 hours.

10. An electromagnetic shielding composite material for winding molding process prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • MXene polyimide composite film and preparation method thereof

    CN115819810A

  • Epoxy resin material for wet winding and preparation method thereof

    CN116162327A

  • Preparation method of electromagnetic shielding anti-static heat conduction material

    CN117487322A

  • Electromagnetic shielding material and method for producing the same

    US20200029477A1